Survey of vehicle emissions in the City of Balsas – MA (Research, Society and Development, 2021)
This paper presents a vehicle data survey carried out from field data collection, through the transfer of local vehicle data with the help of studies collected in the bibliography, surveys on the websites of the Traffic Department of Maranhão (DETRAN - MA) of Balsas and data transported by the Environmental Company of the State of São Paulo (CETESB). Thus, a survey of data on the circulating fleet in the city of Balsas - MA was carried out, total locations were calculated as provided in some roads in the city and compared with the number of vehicles, their possible and pollutants released by type of vehicle. They were evaluated free of carbon dioxide (CO2), methane gas (CH4), carbon monoxide (CO), non-methane hydrocarbons (NMHC), nitrogen oxides (NOx), aldehydes (RCHO) and particulate matter (MP). In the survey of exits on the Luís Gomes and São Pedro roads, the vehicles with the greatest aggregates were motorcycles, followed by automobiles. The largest amounts of diversion (CO2) and (CO) came from motorcycles. While trucks were the main responsible for the NMHC bases and NOx cars. It is hoped that with this work the problem of vehicular bases will get more presented to the city's environmental agencies for and provide tax incentives to enable the study and mitigations about the atmospheric of Balsas.